Menstrual Cycle Variations Observed in Obese and Normal-Weight Women - Desmawati, Desmawati; Berliani, Hasvia; Utama, Bobby Indra (Indonesian Journal of Human Nutrition, 2024)
Obesity plays a significant role in estrogen production, which can lead to menstrual cycle disorders. This study aimed to determine differences in estrogen levels and menstrual cycles between obese and normal-weight female students at the Faculty of Medicine, Universitas Andalas. This study used the comparative cross-sectional design involving 32 obese respondents and 32 respondents with normal-weight status, selected through a systematic random sampling method. The study was conducted from November 2021 to July 2022. Estrogen levels were measured using the enzyme-linked immune assay (ELISA) method, and the menstrual cycle data were collected via interview. Statistical analysis was performed using an unpaired t-test and a Chi-square test. The results showed no significant difference in estrogen levels between the obese group (188.31±47.56 pg/mL) and the normal-weight group (181.76±51.06 pg/mL) (p > 0.05). However, abnormal menstrual cycles were more common in the obese group (29.7%) compared to the normal group (9.4%), with a p-value of 0.002. In conclusion, there are no differences in estrogen levels between the normal nutrition and obese groups; however, the menstrual cycles of these groups are different.